Istanbul as a Global Financial Center - Bildirci, Melike; Zehir, Cemal; Kayikci, Fazil; Karagoz, Murat; Bakirtas, Tahsin (Cambridge Scholars Publishing, 2017)
This book brings together analyses of a wide range of economic and financial subjects, including any issue related to these broader concepts, such as development, banking crises, energy, and Islamic finance, among others. It offers a clear discussion of the current period of economic transition and the future prospects of developing countries in terms of financial and economic perspectives. It will serve to raise awareness of the important opportunities and risks inherent in the global financial system, and makes a valuable contribution to wider economic debates by identifying the priorities and policy prescriptions that will help countries to realise their potential.